Resistivity Piezocone in the Conceptual Site Model Definition - Riyis, M. T.; Giacheti, H. L. [UNESP] (Brazilian Soc Soil Mechanics & Geotechnical Engineering, 2017)
The management and remediation of contaminated sites are strongly dependent on the diagnosis process during the site characterization program. A Conceptual Site Model (CSM) elaborated by use of high-resolution site characterization (HRSC) tools allows for a detailed diagnosis of geo-environmental issues. The piezocone (CPTu) test is a high-resolution tool that allows several specific sensors to be attached, such as the resistivity module. This hybrid device is called the resistivity piezocone (RCPTu). A simulated geo-environmental site characterization program was performed on a Brazilian erosion site using several tools (direct-push soil samplers, hollow stem auger and RCPTu) to develop the CSM for a site similar to the Brazilian conditions. The aim was to elaborate a detailed stratigraphical profile and verify the applicability of this tool at the studied site. It was noted that the RCPTu data interpretation was consistent with the data from traditional methods, with much more details. Better results were achieved when decision-making occurred on site. It was concluded that the RCPTu is a very useful tool in elaborating a suitable hydrogeological conceptual site model, even for Brazilian conditions, especially in an approach that prioritizes high-resolution geo-environmental characterization.
Keywords: site characterization; in situ testing; stratigraphical logging; soil sampling; RCPTu